Wybrane instrumenty budżetowania w ujęciu tradycyjnym i współczesnym - Bąk, Melania (Selected Instruments of Budgeting in Traditional and Contemporary Formulation, 2005)
Budgeting is very important process, which makes possible to function business unit in market economy. New directions in accounting system implied to development of budgeting process. Among modern Instruments of budgeting very important are activity-based budgeting and activity-based costing. The paper presents range and role selected Instruments of the traditional and contemporary budgeting.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 36-45